China's exchange rate impasse and the weak U.S. dollar - Ronald McKinnon; Gunther Schnabl (Center for Economic Studies and ifo Institute (CESifo), 2008)
Since 2004, China has been backed into a situation where the renminbi is expected to go ever higher against the dollar, and this one-way bet has led to a loss of domestic monetary control. Combined with a more general flight from the U.S. dollar, the resulting monetary explosion in China contributes to the worldwide increase in primary commodity priceswith excess liquidity reminiscent of the global inflation generated by the weak dollar in the 1970s.
Keywords: E31; E61; F31; 330; Inflation; exchange rates; macro policies; current account imbalances; Wechselkurs; Aufwertung; Leistungsbilanz; Zahlungsbilanzungleichgewicht; Inflation; Geldpolitik; China; USA; Welt